SELECTED ATTRIBUTE OF HOUSEHOLDS AND SOCIO-ECONOMIC PATTERN: A CASE STUDY OF THARU VILLAGE (KANGRA VALLEY), TEHSIL NAGROTA BAGWAN, DISTRICT KANGRA, HIMACHAL PRADESH, INDIA - Nikesh Sharma (Journal of Geography, Regional Planning and Development, 2024)
This paper is an attempt to analyze the household attributes and socio-economic pattern of Tharu village located in kangra valley of Nagrota Bagwan tehsil, district Kangra. The people of the present research area reside in the laps of nature. This study investigates nature and design of dwellings and socio-economic condition of this village. This paper searching to unfold the question how people survive in this Himalayan mountainous valley and limited landholding area and how they generate their livelihood? Is geographical factors affects their household pattern, and climatic conditions are mostly mountainous sub-tropical type of climatic region. To answer these above following questions field, visit of the same area has been conducted. This research paper is descriptive in nature. The primary Data were collected from the entire households through interviews, informal discussions and field observation. The Tharu village was investigated and it was found that the subsistence agriculture activities and livestock rearing was the main occupation. Some other interesting facts noticed in this study area such as shifting trends towards horticultural activities. On the context of households, there was higher composition of nuclear families rather than joint families. There is lack of adequate of social infrastructure such as education and health institutions. The paper will be helpful in carrying out the further analysis and showing a way to improve existing socio-economic conditions and household pattern of rural settlement in high Himalayan mountainous region in Himachal Pradesh